Determinants of knowledge regarding self-medication among professional students of the apothecary - Atmadani, Rizka Novia; Hidayati, Ika Ratna; Arum, Dinar Famora (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Background: Self-medication or the use of over-the-counter drugs by the general public, including among professional students, is becoming an increasingly common practice. However, this practice can carry risks if done without adequate knowledge, especially for pharmacist students who will later play a role in providing education related to drug use. Objective: This study aims to identify factors that affect the level of knowledge of pharmacist program students regarding self-medication. Methods: This study was a cross-sectional survey using an online questionnaire, and the recorded data were analyzed using Logistic regression models. In total, 100 (66.7%) of 150 students practised self-medication at least once recently. Results: We observe that female students were more likely to have a higher level of knowledge about self-medication than male students—aOR = 4.52, 95 % CI = 1.41-14.42. Meanwhile, students living alone were less likely to have a higher level of self-medication knowledge than those staying with somebody else —aOR = 0.47, 95 % CI = 0.23-0.97. Conclusion: The effect of students who practised self-medication on a higher level of knowledge about self-medication was significant among students who live with somebody else—aOR =2.85, CI = 1.01-8.01 but not among students who live alone. There are more attempts to educate the students about self-medication and the possible risks of doing self-medication. We suggest a similar study can be observed among students during their bachelor study or in their Professional Program.